The effect of interval training on athletic 100 meter running speed: a meta-analysis study - Vindryani Septayasa; Supriatna Supriatna; Yulingga Nanda Hanief; Teejay D. Panganiban (Journal of Science and Education (JSE), 2022)
This research on the effect of interval training on 100 meter running speed has been widely done in sports. Various researchers explain that interval training is very influential in increasing the speed of running 100 meters, but each study reports different results. This difference causes the need to conduct inclusive data analysis to provide comprehensive information about the importance of interval training to increase 100-meter running speed in athletic athletes. This method must be done by collecting data from research results indexed on Google Scholar by searching for research published in the range of 2010-2021. The search for the results of this study was carried out by entering two keywords, namely the first keyword "interval" AND "100 meter run" AND "journal" OR "journal" with the results found 224 articles and the second keyword is "interval" AND "100 meter sprint" with the results found 139 articles. Data on articles that already fit the study's inclusion and exclusion criteria were taken to determine the effect size (ES) and standard error (SE) values. The results of this study show the value of the RE estimate and FE model 11.243 junior high school criteria and the value of the RE estimate and FE model 9.786 athlete criteria which means that this interval training has a significant effect on the junior high school level and athletes who focus specifically on 100 meter running speed. This research is only limited to 100-meter sprints in junior high school students and athletes, it is recommended that future researchers examine other sports and other subjects.